Scenario guidance (narratives and national modelling) succesfully supports policy development in Lao PDR - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The CCAFS Scenarios Project worked closely together with FAO (the SAMIS project and the Flexible Multi-Partner project) to support the government of Lao PDR (Ministry of Agriculture) in the use of scenario-based land use mapping for policy guidance, in a systemic manner focused on internal capacity for applying this scenario-based approach to multiple policies. The Lao PDR Agricultural Development Strategy 2021 to 2030 is being supported by this process.